امیت رسولﷺ اور مستشرقین:منٹگمری واٹ اور رابرٹ اسپنسر کے افکار کا تجزیاتی مطالعہ: Orientalists on Prophet Muhammad’s Illiteracy: A Study of Montgomery Watt and Robert Spencer’s views (Al-Qamar, 2021)
Holy Qur'an has been a topic of interest to many circles, including the Muslim and Western scholars. Many of the themes promoted by the Orientalists are generally related to the authenticity of the Qur'an. William Montgomery Watt and Robert Spencer are included in the circle of those western writers who have written down the commentary of the Quran with specific purpose. While interpreting the verses, they have mistranslated the term “Ummī” and have offered different views on the meaning of "Ummī" which is used in the Qur’an as an attribute of the Prophet (PBUH). This word shows the miraculous signs of the heavenly Book descended upon the Prophet and the rightfulness of his mission but the aim of both the scholars is to prove false the claim of the miraculous style of the Qur’an. In this paper, an effort has been made to examine the arguments of both western scholar and deduce the actual position in this matter. In this research written with a descriptive and analytical approach, it is proved that according to Quran, sciences of Tafsir, Hadith literature, history and logic, Prophet Muhammad was illiterate since his birth until his death and did not know how to read or write.
Keywords: Watt; Spencer; Muhammad; Orientalists; "Ummī"